Management of soil borne diseases of safflower through seed dressing with new fungicide molecules and biopolymer based Trichoderma: Management of soil borne diseases of safflower through seed dressing with new fungicide molecules and biopolymer based Trichoderma - D R MURUMKAR; H N AIWALE; L N TAGAD; S I TAMBE (Journal of Oilseeds Research, 2023)
A field experiment was conducted for two consecutive rabi seasons during 2020-21 and 2021-22 to evaluate the new fungicide molecules and biopolymer based Trichoderma as a seed dressers for management of soil borne diseases of safflower. Among the different treatments, seed treatment with Penflufen 13.28% w/w + Tryfloxistrobin 13.28%w/w FS @ 1ml/kg seed was found most effective as it recorded significantly highest germination (96.5%), least incidence of Fusarium wilt (5.4%) and Macrophomina root rot (5.6%) and significantly highest seed yield (1103 kg/ha), net monetary returns (Rs.33940/-) and B:C ratio (2.69), however, it was statistically at par with seed treatment of biopolymer based T. harzianum, Th4d@10 ml/kg seed (1017 kg/ha) and seed treatment with T. harzianum, Th4d WP @ 10g/kg seed (948 kg/ha) for seed yield.